Monocyte Trafficking and Polarization Contribute to Sex Differences in Meta-Inflammation - Varghese, Mita; Clemente, Jeremy; Lerner, Arianna; Abrishami, Simin; Islam, Mohammed; Subbaiah, Perla; Singer, Kanakadurga (Frontiers in Endocrinology, 2022)
Obesity is associated with systemic inflammation and immune cell recruitment to metabolic tissues. Sex differences have been observed where male mice challenged with high fat diet (HFD) exhibit greater adipose tissue inflammation than females demonstrating a role for sex hormones in differential inflammatory responses. Circulating monocytes that respond to dietary lipids and chemokines and produce cytokines are the primary source of recruited adipose tissue macrophages (ATMs). In this study, we investigated sexual dimorphism in biological pathways in HFD-fed ATMs from male and female mice by RNA-seq. We also conducted chemotaxis assays to investigate sex differences in the migration of monocytes isolated from bone marrow from male and female mice toward a dietary saturated lipid — palmitate (PA), and a chemokine — monocyte chemoattractant protein 1 (MCP1), factors known to stimulate myeloid cells in obesity. ATM RNA-Seq demonstrated sex differences of both metabolic and inflammatory activation, including pathways for chemokine signaling and leukocyte trans-endothelial migration. In vivo monocyte transfer studies demonstrated that male monocytes traffic to female adipose tissue to generate ATMs more readily. In chemotaxis assays, lean male monocytes migrated in greater numbers than females toward PA and MCP1. With short-term HFD, male and female monocytes migrated similarly, but in chronic HFD, male monocytes showed greater migration than females upon PA and MCP1 stimulation. Studies with monocytes from toll-like receptor 4 knockout mice (Tlr4-/-) demonstrated that both males and females showed decreased migration than WT in response to PA and MCP1 implying a role for TLR4 in monocyte influx in response to meta-inflammation. Overall, these data demonstrate the role of sexual dimorphism in monocyte recruitment and response to metabolic stimuli that may influence meta-inflammation in obesity.